Serum aldosterone is associated with mortality and re‐hospitalization in patients with reduced ejection fraction hospitalized for acute heart failure: analysis from the EVEREST trial. (November 2013) - Girerd, Nicolas; Pang, Peter S.; Swedberg, Karl; Fought, Angela; Kwasny, Mary J.; Subacius, Haris; Konstam, Marvin A.; Maggioni, Aldo; Gheorghiade, Mihai; Zannad, Faiez; ,
<x xml:space="preserve">Abstract</x> Aims Post‐discharge morbidity and mortality for acute heart failure (AHF) patients remains high. Although the adverse effects of neurohormonal activation are well known in chronic HF, the prognostic significance of serum aldosterone in patients hospitalized for AHF has not been well studied. Methods and results A secondary analysis was carried out of the placebo arm (n = 1850) from the EVEREST trial which had aldosterone measured at baseline. All patients were hospitalized for worsening HF and had an LVEF <40%. The median follow‐up was 9.9 months. The association between serum aldosterone levels at baseline and the independently adjudicated outcomes [all‐cause mortality (ACM) and the combined outcome of cardiovascular mortality (CVM) and HF re‐hospitalization] were explored with multivariable Cox models. Median aldosterone levels increased during the hospital stay from 11 ng/dL at baseline to 15 ng/dL at discharge (P < 0.001) and remained increased after discharge (16 ng/dL at 24 weeks, P < 0.001). After adjusting for potential confounders, higher baseline aldosterone levels were associated with an increased risk for ACM and CVM or HF re‐hospitalization [hazard ratio (HR) 1.49, 95% confidence intrerval (CI) 1.11–1.99; and HR 1.40, 95% CI 1.11–1.78, respectively, in the highest quartile when compared with the lowest]. Conclusion In patients with LVEF <40% hospitalized for AHF and receiving standard therapy, serum aldosterone levels correlated with worse post‐discharge outcomes. Aldosterone levels increase during AHF hospitalization and remain increased long after discharge. These results suggest that further modulation of the renin–angiotensin–aldosterone system in patients admitted with worsening HF might favourably improve post‐discharge outcomes.